ПРОБЛЕМА ВИВЧЕННЯ ЦІННІСНО-СМИСЛОВОЇ СФЕРИ ОСОБИСТОСТІ У ПСИХОЛОГІЧНИХ ДОСЛІДЖЕННЯХ: ТЕОРЕТИЧНИЙ АСПЕКТ - Melnychenko, А. (Continuing Professional Education: Theory and Practice, 2019)
The article discusses theoretical and methodological approaches to the study of valuesemantic spheres of the individual. The analysis of the basic theories and concepts of the study phenomenon based on the works of A. Adler, D. Leontief, W. Frankl, Maslow, S.L. Rubinstein. Formed the overall picture of understanding the concept of value-semantic sphere of personality in the psychological literature